2015
DOI: 10.1260/1747-9541.10.2-3.379
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Youth Sport: A Qualitative Investigation of Gymnastics Coach and Athlete Perceptions

Abstract: Sport presents an opportunity for young people to experience the joys of success and cope with setbacks to develop resilient behaviours. However, there is a lack of clarity about how sport can cultivate resilience, particularly within a female youth gymnastics context. The purpose of this study was to investigate gymnast and coach perceptions about the development of resilience through gymnastics participation. Underpinned by a qualitative framework, 22 female gymnasts and seven gymnastics coaches participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 36 publications
3
42
0
4
Order By: Relevance
“…These results agree with studies on the effect on the self-efficacy of the feedback offered by coaches, where it is found that moderate negative feedback can have a negative modulating effect on the perception of the athlete's effectiveness and on their capacity for coping (De la Vega, Ruiz-Barquín, Fuentealba & Ortín, 2012b, De la Vega, Ruiz-Barquín, Batista, Ortín & Giesenow, 2012c. In addition to the study by White and Bennie (2015), a study by Howard and Johnson (2004), should also be highlighted which focuses on the characteristics that teachers have in dealing with stressful situations, instead of focusing on those who have suffered acute episodes of burnout, finding, among other relevant results, that high scores in resilience, measure the link between work stress and potential burnout, this being of interest in current research in sports psychology (De Francisco, Garcés de los Fayos & Arce, 2014, Harris & Watson, 2014, Mandigan, Stoebery Passfield, 2015, Vitali, Bortili, Bertinato, Robazza, & Schena, 2015.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results agree with studies on the effect on the self-efficacy of the feedback offered by coaches, where it is found that moderate negative feedback can have a negative modulating effect on the perception of the athlete's effectiveness and on their capacity for coping (De la Vega, Ruiz-Barquín, Fuentealba & Ortín, 2012b, De la Vega, Ruiz-Barquín, Batista, Ortín & Giesenow, 2012c. In addition to the study by White and Bennie (2015), a study by Howard and Johnson (2004), should also be highlighted which focuses on the characteristics that teachers have in dealing with stressful situations, instead of focusing on those who have suffered acute episodes of burnout, finding, among other relevant results, that high scores in resilience, measure the link between work stress and potential burnout, this being of interest in current research in sports psychology (De Francisco, Garcés de los Fayos & Arce, 2014, Harris & Watson, 2014, Mandigan, Stoebery Passfield, 2015, Vitali, Bortili, Bertinato, Robazza, & Schena, 2015.…”
Section: Introductionsupporting
confidence: 90%
“…This data highlights important gaps in knowledge about this matter, particularly relevant being the development of specific studies, since it is coaches who spend more time and have more interaction with the athletes and who are ultimately responsible for maximizing the possibilities of expression and development of resilience in these athletes. The qualitative study by White and Bennie (2015) stands out, with 7 coaches of 22 female gymnasts, finding that environment characteristics, interpersonal relations and the trainer's positive behavior all help in the optimal coping of adverse situations. These results agree with studies on the effect on the self-efficacy of the feedback offered by coaches, where it is found that moderate negative feedback can have a negative modulating effect on the perception of the athlete's effectiveness and on their capacity for coping (De la Vega, Ruiz-Barquín, Fuentealba & Ortín, 2012b, De la Vega, Ruiz-Barquín, Batista, Ortín & Giesenow, 2012c.…”
Section: Introductionmentioning
confidence: 99%
“…Gymnastics is one of the sports activities that is taught to sports students (Coppola, Vastola, Scatigna, & Fabiani, 2015). Gymnastics is a game that consists of quite a few disciplines: creative gymnastics, rhythmic gymnastics, cardio gymnastics, acrobatic gymnastics and tramp lining (White & Bennie, 2015). In addition to an extremely right vary of youthful gymnasts taking part in gymnastics; the variety of male athletes competing at the amusement and collegiate tiers is reportedly on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Some research shows that early specialisation sports can create positive development (Fraser-Thomas & Côté, 2009;Fraser-Thomas, Cote, & Deakin, 2005;Holt & Neely, 2011;Stirling, Cruz, & Kerr, 2012), including in artistic sports (White & Bennie, 2015). However, the majority of empirical literature, and in recent years frequent media reports and personal disclosures, tell of the negative impact artistic sports have on athletes.…”
Section: Introductionmentioning
confidence: 99%